Beryllium foils for windows in counter of nuclear radiation - Papirov, I.I.; Nikolaenko, A.A. (Вопросы атомной науки и техники, 2013)
Based on the optimization of the main structural characteristics (grain structure, texture, dislocation substructure) are defined modes of deformation and heat treatment of beryllium foils (purity > 99.95%), providing their excellent mechanical properties and optimized modes of deformation and heat treatment. Analyzed various technological methods rolling foils to their rational use for the practical implementation of the results of the study. It is shown that the strength and plastic properties of the foils beryllium higher than that of similar foils foreign manufacture.